A benzothiadiazole-based Pt(ii) coordination polymer as an efficient heterogeneous photocatalyst for visible-light-driven aerobic oxidative coupling of amines. Issue 22 (24th February 2023) - Ahmed, Shakil; Kumar, Atul; Mukherjee, Partha Sarathi
Abstract : A solid-state emissive supramolecular coordination polymer (TBP) with multiple benzothiadiazole units selectively converts benzylamines to their corresponding imines under visible light within 2 hours at room temperature. Abstract : An emissive Pt(ii ) coordination polymer (TBP) was synthesized by assembling a benzothiadiazole-based Pt(ii ) acceptor (A ) with a tetraphenylethene (TPE) containing donor (L ). Multiple benzothiadiazole units in the polymeric array of the TBP rendered it with reactive oxygen species generation ability. TBP was found to be an excellent photocatalyst for oxidative coupling of benzylamine under visible light with full conversion within 2 hours at room temperature and reusability for multiple cycles. Such photocatalytic efficiency under ambient conditions, reusability of the catalyst, and easy separation of the product are noteworthy.